Analisis Potensi Pengembanngan Usaha Peternakan dan Mengukur Profitablitas: Analisis Benefit-Cost pada Usaha Peternakan Itik di Indramayu - Nuralfiyani, Amelia; Herlina, Linda; Firman, Achmad (Universitas Galuh, 2024)
Duck farming is a poultry commodity that has potential to be developed. This is supported by the ability of ducks as livestock that produce eggs and meat, so they can meet food needs for animal protein sources. It is hoped that the duck farming business will not only be a side business, but also a profitable business activity. Indramayu Regency was chosen deliberately, because it has one of the potentials for developing ducks. The criteria for testing the efficiency of a duck farming business are: R/C Ratio for a duck farming business > 1, so the business is efficient; R/C Ratio of duck farming business = 1, then the business is not efficient; The R/C Ratio for a duck farming business is <1, so the business is inefficient. The average value of economic efficiency (R/C Ratio) in duck farming businesses in Sindang District is 1.22. The average annual income of duck breeders is IDR 32,522,175. This income is obtained from the difference between the total income from the duck farming business and the costs used during the production process. The level of potential for development of the duck farming business in Sindang sub-district by evaluating the general conditions in Sindang sub-district. Based on calculations, a total internal factor score of 3.308 was obtained and a total external factor score of 3.263.